Side Effects from Cancer Therapies and Perspective of 1044 Long-Term Ovarian Cancer Survivors-Results of Expression VI-Carolin Meets HANNA-Holistic Analysis of Long-Term Survival with Ovarian Cancer: The International NOGGO, ENGOT, and GCIG Survey - Woopen, Hannah; Keller, Maren; Zocholl, Dario; Mittelstadt, Suzana; Barretina-Ginesta, Maria-Pilar; Heinzelmann-Schwarz, Viola; Lafleur, Judith; Kocián, Roman; Baum, Joanna; Krabisch, Petra; Achimas-Cadariu, Patriciu; Vardar, Mehmet Ali; et al. (Cancers, 2023)
The aim of this survey was to increase the knowledge on the characteristics and health concerns of long-term survivors (LTS; survival > 5 years) after ovarian cancer in order to tailor follow-up care. This international survey was initiated by the NOGGO and was made available to members of ENGOT and GCIG. The survey is anonymous and consists of 68 questions regarding sociodemographic, medical (cancer) history, health concerns including distress, long-term side effects, and lifestyle. For this analysis, 1044 LTS from 14 countries were recruited. In total, 58% were diagnosed with FIGO stage III/IV ovarian cancer and 43.4% developed recurrent disease, while 26.0% were receiving cancer treatment at the time of filling in the survey. LTS who survived 5-10 years self-estimated their health status as being significantly worse than LTS who survived more than 10 years (p = 0.034), whereas distress also remained high 10 years after cancer diagnosis. Almost half of the cohort (46.1%) reported still having symptoms, which were mainly lymphedema (37.7%), fatigue (23.9%), pain (21.6%), polyneuropathy (16.9%), gastrointestinal problems (16.6%), and memory problems (15.5%). Almost all patients (94.2%) regularly received follow-up care. Specialized survivorship care with a focus on long-term side effects, lifestyle, and prevention should be offered beyond the typical five years of follow-up care.
Keywords: follow-up care; survivorship: long-term survivors; ovarian cancer; long-term side effects